Trust on Sharia M-Banking: Evidance on Milenials Generations - Novita Safitri; Wahyu Anggraini (Journal of Islamic Economic Scholar, 2021)
This study aims to examine the trust of millennial generation in the role of sharia mobile banking in the ease of solving their financial problems. The increased use of smartphones has made the banking industry provide mobile banking services to facilitate and increase customer productivity. The level of trust in sharia mobile banking is measured using the Technology Acceptance Model (TAM). Based on TAM, trust is determined by Perceived Easy of Use (PEoU), Perceived Usefulness (PU), Attitude to Product (ATP), and Intention to Use (ITU). This study uses an independent survey, with a total sample of 330 sharia mobile banking users spread throughout Indonesia. Data analysis techniques used in this study used SB-SEM (Covariance Based-Structural Equation Modeling) with AMOS software. The results showed that PEoU had a positive effect on PU, PEoU had a positive effect on ATP, PU had a positive effect on ATP, ATP had a positive effect on ITU, and ITU had a positive effect on Trust. Overall millennial generation has a high level of trust in sharia mobile banking, because sharia mobile banking is easy to use and makes it easy to solve their financial problems.